Clinical and genetic correlation of spinocerebellar ataxia patients: Insights from a tertiary care investigation - Bashir Sanie; Atif Kawoosa; Ibrar Ahmed Khan; Sheikh Hilal; Zubair Ul Nazir; Adnan Firdaus Raina (Annals of Movement Disorders)
INTRODUCTION: Spinocerebellar ataxias (SCAs) are a group of neurodegenerative disorders characterized by progressive cerebellar ataxia and various noncerebellar manifestations. This study aimed to investigate the clinical and genetic correlations among patients with SCA at a tertiary care center in Srinagar, Kashmir. METHODS: This cross-sectional study included 93 patients with hereditary and sporadic ataxias. The patients underwent clinical assessments, brain imaging, and genetic testing for SCA1, SCA2, SCA3, SCA6, SCA12, SCA 17, and dentatorubral-pallidoluysian atrophy (DRPLA) using polymerase chain reaction (PCR) and agarose gel electrophoresis. RESULTS: Among the 93 patients, 23.7% were in their second or third decade of life, and 62.4% were male. All patients presented gait ataxia and dysarthria (100%). Cerebellar atrophy was observed in 60.2% of the patients. Genetic testing identified SCA1 in 17.2%, SCA2 in 14%, SCA6 and SCA12 in 1.1% each, SCA17 in 2.2%, and DRPLA in 4.3% of the patients. No cases of SCA3 were found. Clinical manifestations such as slow saccades, nystagmus, dysdiadochokinesia, dysmetria, impaired finger-nose-finger test, and positive Babinski sign were significantly associated with specific genetic subtypes (p < 0.05). However, the radiological findings did not indicate a significant association with genetic subtypes (p = 0.163). CONCLUSION: This study revealed a unique distribution of SCA subtypes in the Kashmiri population, which is characterized by a higher prevalence of consanguinity and distinct clinical and genetic profiles. In the future, multi-center studies with broader genetic testing panels and longitudinal follow-ups are needed to further elucidate the phenotypic and genotypic variations in this population.